Convertible bond markets - Philips, George A. (Basingstoke : Macmillan, 1997)
This book contains Convertible Bonds; Convertible Financing; Payoff Analysis: A Primer for Theoretical Valuation; Fair Value of a Convertible Bond; An Introduction to Interest Rate Sensitivity of Convertible Bonds; Default Risk assessed; Long Volatility; and Multivariate Hedging.
Keywords: Economics; Bonds; Bond market; Convertible bonds